Capital humano y capacidades societales de condiciones para el desarrollo de las empresas de producción social en Venezuela - COLINA ARENAS, Belinda (REVESCO. Revista de Estudios Cooperativos, 2009)
The aim is to highlight the importance of human capital for the development of societal capacities for innovation in CSI Enterprises Production Social EPS through the introduction of an innovative culture, under the conviction of the role that must assume the same in the development and consolidation of these. The EPS arise under the Registry of Companies of Social Production REPS, created in November 2005 inserted in the Program of Social Production Enterprises, as guaranteed in the 3895 decree of September 2005, called Endogenous Development and Social Production Companies (Republica Bolivariana de Venezuela, 2005) and within the framework of Plan Siembra Petrolera 2006-2012; adjudging to Petroleos de Venezuela, SA. As strategic company of the state as a catalytic role in leveraging these modalities socio-productive. The REPS represents an social-institutional innovation and socio-productive Venezuelan and is a key strategy of the Venezuelan state in building support for the social economy in the country. This record has the aim to diversify production, to increase and strengthen the weave of national production and transformation of production relations. For its part the EPS represents an innovation in the social economy in Venezuela, which deepen the values of solidarity both inside these organizations, for their relationship to the socio-economically disadvantaged communities. Used the methodology of hermeneutics philological for analysis and interpretation of official documents and national institutional and specialized national and international literature on the subject, plus an interview. Among its findings: 1) proposal by some theoretical elements for the establishment of an innovative culture in the human capital of the EPS, 2) introduction of the concept of CSI adjusted to the context of the Venezuelan EPS and 3) building a taxonomy CSI for these companies. The most important conclusion is the need to promote a "culture of innovation" in the human capital to strengthen these efforts by developing productive member of CSI.
Keywords: Registration of social production enterprises; Social economy; Innovation culture; Sociocéntric approach; Venezuela